Study of blood group and platelet counts in ER and ENT patients with epistaxis - Pradhan, Binita; Bista, Raunak; Bhattarai, Bharat Kumar; Luitel, Ashaya; Pandey, Sujan; Pradhan, Sailesh (Journal of Pathology of Nepal, 2023)
Background: Epistaxis is one of the most common emergencies and a very difficult problem to tackle especially in Primary Health Centers or Health Posts in rural areas of Nepal. The objective of the study was to identify blood group and platelet count with the occurrence of nasal bleeding. Materials and Methods: A prospective study was carried out among 96 patients visiting Kathmandu Medical College and Teaching Hospital in Emergency Department and ENT Department with epistaxis from October 2021 to October 2022. Ethical clearance was obtained from IRC Kathmandu Medical College Teaching Hospital (reference no: 0609202105). A blood sample was sent for blood groups and platelet count. Convenience sampling was used. Data were entered in Microsoft Excel 2016 and analyzed in Statistical Package for Social Sciences version. Results: The age group of 20-29 years was found to be the commonest age group presented with epistaxis. The commonest blood group with epistaxis was found to be O+ve and platelet count was found to be within the normal range in the majority of the cases. Conclusions: Epistaxis was found to be more common among patients with O+ve than non ‘O’ blood groups. Patients with Blood group O+ve need to be investigated further for coagulation profile before any kind of procedure.